2022
DOI: 10.3389/fmicb.2022.969656
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and short-chain fatty acids may be new biomarkers for predicting neonatal necrotizing enterocolitis: A pilot study

Abstract: BackgroundDysbacteriosis is thought to play an important role in the pathogenesis of necrotizing enterocolitis (NEC). We aimed to identify new biomarkers among gut microbiota and short-chain fatty acids (SCFAs) for the early prediction of NEC.Materials and methodsThirty-four preterm infants with gestational ages of ≤ 34 weeks who developed gastrointestinal symptoms were divided into the NEC group (n = 17) and non-NEC group (n = 17). In the NEC group, the gut microbiota and SCFAs in feces were assessed when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…Substantial evidence has indicated that succinate concentrations increase under conditions of hypoxia, stress, inflammation, and changes in intestinal microorganisms ( Nagao-Kitamoto et al., 2016 ; Macias-Ceja et al., 2019 ; Banerjee et al., 2020 ; Huber-Ruano et al., 2022 ). It has been widely reported in previous studies that changes in the intestinal flora are closely related to the development of NEC ( He et al., 2021 ; Liu et al., 2022a ; Samara et al., 2022 ). In exploring the pathological mechanism whereby the gut flora affects NEC, some investigators have proven that gut microbiota-derived metabolites, including short-chain fatty acids, DL-lactate, tauroursodeoxycholic acid, and other related metabolites, play important messenger roles in NEC progression or can contribute to its prediction ( Li et al., 2019a ; Feng et al., 2022 ; Huang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial evidence has indicated that succinate concentrations increase under conditions of hypoxia, stress, inflammation, and changes in intestinal microorganisms ( Nagao-Kitamoto et al., 2016 ; Macias-Ceja et al., 2019 ; Banerjee et al., 2020 ; Huber-Ruano et al., 2022 ). It has been widely reported in previous studies that changes in the intestinal flora are closely related to the development of NEC ( He et al., 2021 ; Liu et al., 2022a ; Samara et al., 2022 ). In exploring the pathological mechanism whereby the gut flora affects NEC, some investigators have proven that gut microbiota-derived metabolites, including short-chain fatty acids, DL-lactate, tauroursodeoxycholic acid, and other related metabolites, play important messenger roles in NEC progression or can contribute to its prediction ( Li et al., 2019a ; Feng et al., 2022 ; Huang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, with the change in the gut microbiota, metabolites show corresponding changes; the affected metabolites are generally considered to act as a bridge between flora and host communication and may also be involved in the pathogenesis of NEC (Krautkramer et al, 2021;Zhou et al, 2022a). For example, several studies have demonstrated the effect of short-chain fatty acids on the progression of intestinal health in patients with NEC and demonstrated that they show predictive value for NEC development (Roy et al, 2018;Sun et al, 2021;Liu et al, 2022a). Succinate, widely regarded as an intermediate molecule of the mitochondrial tricarboxylic acid cycle, has recently emerged as a key player in maintaining intestinal homeostasis, intestinal energy metabolism, and immune regulation (De Vadder et al, 2016;Banerjee et al, 2020;Zhou et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm infants demonstrated a significantly less diverse microbiome, including Bifidobacterium spp. [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Bifidobacterium spp.…”
Section: Insights Into the Scfa-producing Bacteria In Preterm Infantsmentioning
confidence: 99%
“…The aetiology of NEC is not clear, but it is thought to be related to several factors, including pre-eclampsia, aberrant bacterial colonization (e.g., infection), premature rupture of the membranes, placental abruption, intrauterine growth restriction, LBW, patent ductus arteriosus, sepsis and anemia [ 13 ]. Early gut microbial dysbiosis is also implicated in disease pathogenesis, in which the gut microbiota composition of preterm infants with NEC is characterized by reduced abundances of Bifidobacterium , Firmicutes and Bacteroidetes and increased abundances of Prevotella , Clostridioides , Staphylococcaceae , Proteobacteria , Enterobacteriaceae , Rothia , Streptococcus and Blautia [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%